Design, Synthesis and Applications of Hyaluronic Acid-Paclitaxel Bioconjugates† - Leonelli, Francesca (Molecules, 2008)
Paclitaxel (1a), a well known antitumor agent adopted mainly for the treatment of breast and ovarian cancer, suffers from significant disadvantages such as low solubility, certain toxicity and specific drug-resistance of some tumor cells. To overcome these problems extensive research has been carried out. Among the various proposed strategies, the conjugation of paclitaxel (1a) to a biocompatible polymer, such as hyaluronic acid (HA, 2), has also been considered. Coupling a bioactive compound to a biocompatible polymer offers, in general, many advantages such as better drug solubilization, better stabilization, specific localization and controlled release. Hereafter the design, synthesis and applications of hyaluronic acid-paclitaxel bioconjugates are reviewed. An overview of HA-paclitaxel combinations is also given.